Analysis of obstetric care provided by the Mobile Emergency Care Service - Michilin, Nathallia Serodio [UNESP]; Jensen, Rodrigo [UNESP]; Jamas, Milena Temer [UNESP]; Pavelqueires, Shirlene; Garcia de Lima Parada, Cristina Maria [UNESP] (Assoc Brasileira Enfermagem, 2016)
Objective: analyze the pertinence of calls made by obstetric users of the Mobile Emergency Care Service (SAMU 192) of Botucatu-SP. Method: retrospective and analytical research. All records of prehospital obstetric care delivered by the SAMU 192 in 2012 were analyzed. To be considered responsive, calls should lead to referral to a reference obstetric hospital or be classified with the colors red, orange and yellow, according to risk criteria defined by the Ministry of Health. Results: considering the two outcomes evaluated: referral to a reference hospital and risk criteria defined by the Ministry of Health, 6.7% and 75.6% of the calls were not pertinent, respectively. There was no matching between outcomes, neither variation between primiparas and multiparas as regards the call pertinence. Conclusion: this study ratifies the need for implementing a risk classification protocol in obstetrics, and support managers in the organization, qualification and effective implementation of the Rede Cegonha.
Keywords: Emergence Medical Services; Emergency Nursing; Prehospital Services; Pregnant Women; Obstetric Nursing